2015
DOI: 10.1590/s1679-87592015081806302
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile fish use of the shallow zone of beaches of the Cananéia-Iguape coastal system, southeastern Brazil

Abstract: The purpose of the present study is to describe the juvenile fish use of the shallow zone of beaches of the Cananéia-Iguape coastal system, São Paulo, Brazil, analyzing its occurrence period and the patterns of utilization for the most abundant species. Using a beach seine monthly for one year, we sampled 13861 individuals, of 57 species and 24 families. The fish species used the study area for different proposes: Atherinella brasiliensis was sampled in all phases of gonadal development and considered as resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…The Mugilidae Mugil curema (Valenciennes, 1836) presented relevant species score. The species M. curema is usually found in reef environments (Lieske & Muers 1994), but only uses these areas as a passage to estuarine regions (Favero & Dias 2015), which is in agreement with our observation of large schools during only one day. Despite M. curema abundance of more than 50 individuals, and its association to substrate covered by zoanthids, this relationship was probably biased due to the species' occasional presence on rocky shores.…”
Section: Discussionsupporting
confidence: 92%
“…The Mugilidae Mugil curema (Valenciennes, 1836) presented relevant species score. The species M. curema is usually found in reef environments (Lieske & Muers 1994), but only uses these areas as a passage to estuarine regions (Favero & Dias 2015), which is in agreement with our observation of large schools during only one day. Despite M. curema abundance of more than 50 individuals, and its association to substrate covered by zoanthids, this relationship was probably biased due to the species' occasional presence on rocky shores.…”
Section: Discussionsupporting
confidence: 92%
“…The occurrence of all ontogenetic phases of A. brasiliensis in intertidal zones was also observed by Favero and Dias (2015). An in-depth review (Froese 2006) on the weight-length relationship of fish, and a metaanalysis using Bayesian statistics (Froese et al 2014) identified general trends of the weight-length relationship according to body shape.…”
Section: Discussionmentioning
confidence: 95%
“…In the coastal area of the state of Rio Grande do Sul, young mullets are frequently present and abundant in the surf zone throughout the year (Ramos andVieira 2001, Rodrigues et al 2015), which is also the case on the coast of Argentina (Acha 1990, Castellini et al 2017. However, in the northern area of the southern population (state of São Paulo) (Mai et al 2014), the presence of young mullets in the surf zone occurs shortly after the reproductive period, and individuals are less abundant or absent in the surf zone during the remaining months of the year (Favero and Dias 2015). It seems that there is a clinal decrease in surf zone occurrence from the northern to the southern limits of the southern population.…”
mentioning
confidence: 92%